2004
DOI: 10.1264/jsme2.19.215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Symbiotic Flagellate Faunae between Termites and a Wood-Feeding Cockroach of the Genus <i>Cryptocercus</i>

Abstract: Termites of most isopteran families and wood-feeding cockroaches of the genus Cryptocercus usually harbor more than one symbiotic flagellate species in their hindgut. To evaluate the similarity of their symbiont faunae, data on symbiont composition at a generic level were examined by cluster analysis and type III quantification method. In both analyses, the symbiont composition recorded from host insects belonging to the same families or monophyletic family groups tended to be similar. This tendency was partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 16 publications
5
74
0
Order By: Relevance
“…This mode of symbiont transfer is reflected in cospeciation between Pseudotrichonympha species and their host termites (Noda et al 2007) and is also suggested by overall congruence of symbiont composition with host termite phylogeny (Kitade 2004). Vertical transmission via proctodeal trophallaxis in a common ancestor of Cryptocercus and termites probably originated from intraspecific coprophagous behaviour in aggregations; coprophagy is common in many studied cockroaches and plays a role in the horizontal transfer of their gut microbiota.…”
Section: Discussionmentioning
confidence: 87%
“…This mode of symbiont transfer is reflected in cospeciation between Pseudotrichonympha species and their host termites (Noda et al 2007) and is also suggested by overall congruence of symbiont composition with host termite phylogeny (Kitade 2004). Vertical transmission via proctodeal trophallaxis in a common ancestor of Cryptocercus and termites probably originated from intraspecific coprophagous behaviour in aggregations; coprophagy is common in many studied cockroaches and plays a role in the horizontal transfer of their gut microbiota.…”
Section: Discussionmentioning
confidence: 87%
“…The protist symbionts in the hindguts of Cryptocercus cockroaches and lower termites were long suspected to have codiversified with their hosts (15,17,49). The common ancestor of Cryptocercus cockroaches and termites is thought to have evolved a dependence on a specialized consortium of gut microbes that allowed it to gain nutrition from the consumption of wood (16,50).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Reticulitermes species but not the other rhinotermitids are known to harbor oxymonad protists (53). The distinctness of the parabasalid community in the hindguts of Reticulitermes species, in partic- ular the occurrence of Trichonympha closely related to those in Archotermopsidae, suggests that symbiont transfer has had a significant role in structuring these communities (49).…”
Section: Discussionmentioning
confidence: 99%
“…Among insects, the bacterial gut communities of termites, beetles and wood roaches have been studied extensively but the fungal communities are less well known. Most studies of gut inhabitants of wood roaches, Cryptocercus (Blattodea: Cryptocercidae), have focused on enumeration of bacteria, especially endosymbiontic bacteria, and protists without mention of fungi that may have been present (Sacchi et al 1998;Clark and Kambhampati 2003;Kitade 2004;Maekawa et al 2005;Noda et al 2006;Klass et al 2008;Berlanga et al 2009;Carpenter et al 2009;Ohkuma et al 2009;Carpenter et al 2010Carpenter et al , 2011. One study, however, reported the isolation of a yeast species from Cryptocercus punctulatus (Prillinger et al 1996, Prillinger andKö nig 2006).…”
Section: Introductionmentioning
confidence: 99%